Savings education: Learning the value of self-control. - Hutton, Patricia A.; Holmes, James M. (Education Policy Analysis Archives, 2005)
This article proposes a funded school-based allowance and savings program targeted at economically disadvantaged students with poor educational outcomes to help poor children develop less present-biased time preference patterns so as to increase student effort and skills acquisition, avoid the pitfalls that pave the path of adolescence and move from poverty to middle class status as adults. Time orientation is associated with low educational investments, poor educational outcomes, out-of wedlock and teenage childbirth, criminality, and poverty, and nothing better characterizes the role of time preferences in distinguishing socioeconomic classes than attitudes and behavior with respect to money income. In poverty, money income is to be spent whereas in the middle class and the wealthy, money is to be managed and invested and children are taught the value of self-control and delayed gratification through the accumulation, savings and investment of regular allowances. We propose a model program parameterized in a way that children, given complete freedom of choice, should develop more future oriented preferences resulting in greater effort and skills acquisition in school, and the habits of conduct necessary for productive work life. Program cost, which cannot exceed program design, can be reasonably anticipated and is directly related to the benefit - the more that a child saves, the higher the cost, but the more likely that the child has acquired a future time orientation. We present evidence that even if the estimated maximum disbursements occurred and only a minimal percent of participating students changed their lives, the estimated benefits should outweigh disbursement costs.